2012
DOI: 10.1590/s0074-02762012000300012
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of new terpenoid derivatives against Leishmania infantum and Leishmania braziliensis

Abstract: The activity of five (1)(2)(3)(4)(5)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…On the other hand, semisynthetic ferruginol analogues 3 (Fig. 1) displayed antileishmanial activity (IC50= 22.3-35.0 µM) on intracellular amastigotes (L. infantum and L. braziliensis), being more active and less toxic than the reference drug glucantime [7]. Recently, Moreira et al reported on the antileishmanial activity of some dehydroabietic acid derivatives (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, semisynthetic ferruginol analogues 3 (Fig. 1) displayed antileishmanial activity (IC50= 22.3-35.0 µM) on intracellular amastigotes (L. infantum and L. braziliensis), being more active and less toxic than the reference drug glucantime [7]. Recently, Moreira et al reported on the antileishmanial activity of some dehydroabietic acid derivatives (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…1. The collection comprised the parent compound 1, its amide derivative 2, and compounds built from 1 using carbodiimide coupling and base hydrolysis 26,27 with L-amino acid derived side-chains, namely, compounds 3-19, and with D-amino acid side-chains (compounds [20][21][22][23][24][25][26][27][28][29][30][31]. Two additional compounds 17 and 29 were synthesized to complete the set, following the same procedures.…”
Section: Resultsmentioning
confidence: 99%
“…berries have also been reported to have antiprotozoal properties. [20][21][22][23][24] However, in some cases the testing was made only for extracellular parasitic forms whereas in others the compounds were either inactive or displayed limiting toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…amazonensis intracellular amastigotes [ 44 ]. Ramirez-Macias et al [ 45 ], on the other hand, obtained the IC50 against intracellular amastigotes of Leishmania infantum chagasi at a 31.1 μM Glucantime concentration.…”
Section: Discussionmentioning
confidence: 99%